A PSYCHOLINGUISTIC STUDY ON COMMUNICATION IMPAIRMENTS BY AN AUTISTIC CHILD WITH PDD-NOS AT SLB MUHAMMADIYAH SIDAYU GRESIK - FIMAWATI, YULI (Jurnal Ilmiah Mahasiswa FIB, 2013)
Every person needs language to express something from someone to someone else, which is communication. Communication will be successful if the speakers and the hearers are successfully producing and comprehending the speech. In this case, an autistic child is unable to communicate successfully because he has difficulty in understanding speech. This research aims to investigate about: (1) the types of communication impairments and (2) the patterns of nonverbal communication done by an autistic child with PDD-NOS at SLB Muhammadiyah This study obtained the data through on observation and video recordings of interactions by the autistic student and his teacher at school. The participant was a student at grade three SDLB with PDD-NOS. NIDCD (2010) is the theory that used to analyze the types of communication impairments, and the theory of Ambady and Rosental (1998) is used to analyze the types of Non-Verbal communication.Sidayu Gresik.The result of this study shows that the student had communication impairments and difficulty in nonverbal communication. In communication impairments the student had four types of communication impairments namely repetitive or rigid language, narrow interests, uneven language development, and poor nonverbal language. The dominant communication impairments appeared was repetitive or rigid language with 30 occurrences. Moreover, the student has poor nonverbal communication since there where 32 situations in which he did not use nonverbal language in his communication.In conclusion, the student has difficulties to use and understand the context of the communication. There are four types with 46 occurrences in communication impairments, 32 situations with three types of nonverbal communication are by the participant. He had difficulties to use and understanding the meaning of the communication. So, it will be better to use simple instructions and sentences to communicate with children with PDD-NOS.Beside, the next researcher will be good to investigate how the way people with PDD-NOS can product and comprehension the language as the normal people do. Keywords: Psycholinguistics, Communication impairments, Pervasive developmental disorder-not otherwise specified, Sekolah Biasa Luar Muhammadiyah Sidayu Gresik.